From the European Youth Olympics Festival to professional sport. The level of athlete dropout – a longitudinal cohort study - Kovács, Krisztina; Pignitzky, Dorottya; Bartha, Csaba; Takács, Johanna (Frontiers in Psychology, 2025)
BackgroundGlobally, the dropout rate among young athletes, which is influenced by a range of complex and interconnected factors, tends to rise significantly when adolescence starts.ObjectiveThe present retrospective cohort study aimed to explore the characteristics and extent of dropout in youth sports in Hungary.MethodsWe analysed the status of 409 athletes who participated in the summer editions of the European Youth Olympic Festival (EYOF) between 2009 and 2019, assessing their athletic status 5 years later. Specifically, we examined the associations between dropout rates and factors such as gender, types of sport and relative age quartiles.ResultsOur findings reveal that dropout rates were higher in individual sports compared to team sports. Additionally, within individual sports, athletes born in the second age quartile had a slightly higher dropout rate, while those born in the third quartile experienced a slightly lower rate compared to the other quartiles.ConclusionThese insights contribute to a deeper understanding of the factors influencing dropout in youth sports.